Vascular Neoplasms and Malformations Involving the Airway - Harris, George F., IV; White, David R. (Facial Plastic Surgery, 2012)
Vascular anomalies fall into two groups: vascular neoplasms and vascular malformations. Their behaviors differ, therefore they require different methods of management. Vascular lesions of the airway involve some degree of airway obstruction, although this may not be their primary manifestation. Areas of narrowing along this pathway have functional consequences for respiration, swallowing, speech, and growth, as well as overall development and quality of life. Small amounts of airway narrowing may be significant, and there are important differences between the adult and pediatric airway. Although lesions can be distractingly large, deforming, or completely hidden from view, the clinician should focus on evaluating for impairments of function. Awake flexible fiberoptic laryngoscopy is the first diagnostic step. Imaging is critical to both diagnosis and management of vascular anomalies, as specific diagnoses lead to varying treatment options. Management of vascular anomalies of the airway requires knowledge of treatment options and multidisciplinary care.
Keywords: vascular neoplasms; vascular malformations; airway lesions; airway hemangioma; postcricoid hemangioma